Phosphine-Catalyzed Asymmetric [3+2] Cyclization of Oxetane MBH Carbonates and Thioaurones - Ding, Shuo; Han, Xiao; Wang, Zhen; Yao, Weijun (Synthesis, 2025)
We have successfully applied 3-oxetanone-derived MBH carbonates in the phosphine-catalyzed asymmetric [3+2] cyclization with activated thioaurones. With l-threonine-derived amide phosphine as the catalyst, a series of oxetane bis-spiro cyclopentene skeletons, involving two spiral scaffold with vicinal tertiary and quaternary stereocenters, were constructed in good yield with good enantioselectivity and moderate to good diastereoselectivity.
Keywords: Oxetane; Phosphine; Asymmetric; [3+2] cyclization; Thioaurones; Bis-spiro